Bacterial biofilm and extracellular polymeric substances in the treatment of environmental pollutants: Beyond the protective role in survivability. (15th December 2022) - Mahto, Kumari Uma; Vandana,; Priyadarshanee, Monika; Samantaray, Devi P.; Das, Surajit
Abstract: Increased tolerance to toxic pollutants and enhanced degradation capabilities of the bacterial biofilm is often attributed to the matrix of extracellular polymeric substances (EPS). This biopolymeric matrix provides structure, stability, and shelter to the cells within a biofilm and the major constituent of this matrix is exopolysaccharides. However, the role of EPS extends beyond offering protection to the bacterial cells under stress. Bacterial EPS exhibits a double-layered structure consisting of the loosely bound EPS (LB-EPS) and the tightly bound EPS (TB-EPS). Both these EPS layers interact with noxious environmental pollutants through emulsification, solubilization, binding, precipitation, complexation, and ion exchange. Different functional groups of EPS, such as carboxyl, amide, phosphoryl, and hydroxyl, are involved in the removal of toxic pollutants from contaminated environments. Biofilm-EPS participate in several remedial functions such as sequestration of heavy metals, emulsification of petroleum hydrocarbons, binding and solubilization of polycyclic aromatic hydrocarbons (PAHs), and sorption and degradation of dyes and pesticides. Thus, bacterial biofilm and EPS present an attractive solution for decontaminating heavily polluted environments. This review discusses a comprehensive account of biofilm physiology, EPS components, and synthesis mechanisms of exopolysaccharides. The interaction mechanisms of bacterial biofilm and EPS with pollutants have been discussed in detail, and the application of biofilm-forming bacteria and associated EPS in the bioremediation of the environment has been summarized. A deeper understanding of the bacterial biofilm and EPS-mediated pollutant removal will help develop technologies for field-scale applications. Graphical abstract: Image 1 Highlights: Bacterial biofilm exhibits increased tolerance to toxic environments. EPS imparts functional and mechanical stability to the biofilm. EPS-metal interaction occurs via complexation, precipitation and ion exchange. Biofilm-EPS enhances the bioavailability of hydrophobic pollutants to cells. Commercialization of the technology is needed for large-scale applications.